2018
DOI: 10.1007/s10551-018-3898-y
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing Psychological Freedom in Corporate–Community Engagement

Abstract: This article analyses the ethics of how community engagement and dialogue as applied by a mining corporation in Chile led to erosion of the community's psychological freedom despite being aligned with best practice. This article details how a mining company squeezed the psychological freedom of the community in order to obtain an agreement between the period of 2000 and 2016. The findings focus particularly on a 9-month period between 2015 and 2016 when the company undertook intense community engagement. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 42 publications
0
38
0
5
Order By: Relevance
“…These corporate-community sessions could result in codifying and policing the field of possible community responses to extraction rather than fostering meaningful interchange (Lo 2010;Leonard 2016;Murrey 2016). Corporate consultations can be occasions for corporate entities to restrict autonomy of grassroots action by (1) "domesticating opposition or co-opting or transforming it to align more with state or corporate agendas" (Sawyer and Gomez 2012, 5); (2) impeding people's "psychological freedom" by directing decision making into certain corporate-friendly conduits (Maher 2018); (3) producing neoliberal subjectivities that limit the venues and vocabularies in which complaints are either taken seriously or go unrecognized (Leonard 2016); and (4) exacerbating internal community divisions or creating new tensions (Obi 1997;Murrey 2015aMurrey , 2016.…”
Section: Passive and Static Local Support For Extractionmentioning
confidence: 99%
“…These corporate-community sessions could result in codifying and policing the field of possible community responses to extraction rather than fostering meaningful interchange (Lo 2010;Leonard 2016;Murrey 2016). Corporate consultations can be occasions for corporate entities to restrict autonomy of grassroots action by (1) "domesticating opposition or co-opting or transforming it to align more with state or corporate agendas" (Sawyer and Gomez 2012, 5); (2) impeding people's "psychological freedom" by directing decision making into certain corporate-friendly conduits (Maher 2018); (3) producing neoliberal subjectivities that limit the venues and vocabularies in which complaints are either taken seriously or go unrecognized (Leonard 2016); and (4) exacerbating internal community divisions or creating new tensions (Obi 1997;Murrey 2015aMurrey , 2016.…”
Section: Passive and Static Local Support For Extractionmentioning
confidence: 99%
“…Empirical research (e.g. Moog et al, 2015;Coleman, 2013;Himley, 2014;Li, 2016;Maher, 2018;Bo et al, 2018) has indicated that, despite their normative coherence, it seems only an ineffective and simulated governance -or, as Walters calls it, 'anti-politics' (2004, p. 33) -is generated when the dialogical and deliberative potential of those who defend public interests via enterprise strategies is undermined because of their managerial dependency on more operationally capable, and thus, more powerful corporations (see Moog et al, 2015;Lemke, 2007). Another, even more significant issue relates to the underestimation of the state's actual influence, because of PCSR's normative bias and alignment with an 'ideal future', in detriment of a historical assessment of the state's material organization and actual influence (Gond et al, 2011).…”
Section: (Re)encountering the Organized State: From Governance To Govmentioning
confidence: 99%
“…The inequitable distribution of environmental costs means that certain communities experience more environmental risk than others (Maher 2018;Schlosberg 2013). For the people living close to them, wind farms pose many environmental risks, including visual landscape changes, noise, sleep disturbance, and land ionization (Romero et al 2017) (the latter is a phenomenon in which electricity seeps into the land, which negatively impacts livelihoods (Pierpont 2009).…”
Section: Competing Visions Of Environmental Justice (Ej)mentioning
confidence: 99%
“…Building on environmental (in)justice literature (Graff et al 2019;Maher 2018;Walker and Bulkeley 2006;Zárate-Toledo et al 2019), this research discusses a rarely debated consequence of renewable energy investment: the gradual and continuous transformation of indigenous peoples' norms and behaviors away from their traditional economic and cultural livelihoods. The dysfunctional dynamic that exists in governments and businesses in Mexico (Gonzalez and Pérez-Floriano 2015) and other transitioning institutional contexts is also discussed based on the conceptual understanding of the social turbulence of environmental (in)justice, which is defined as the unpredictable behavior of political and social systems when existing laws and regulations are not executed with regard to EJ's tenets.…”
Section: Introductionmentioning
confidence: 99%